De novo Sequencing and Comparative Transcriptomics of Floral Development of the Distylous Species Lithospermum multiflorum - Cohen, James I. (Frontiers in Plant Science, 2016)
Genes controlling the morphological, micromorphological, and physiological components of the breeding system distyly have been hypothesized, but many of the genes have not been investigated throughout development of the two floral morphs. To this end, the present study is an examination of comparative transcriptomes from three stages of development for the floral organs of the morphs of Lithospermum multiflorum. Transcriptomes of flowers of the two morphs, from various stages of development, were sequenced using an Illumina HiSeq 2000. The floral transcriptome of L. multiflorum was assembled, and differential gene expression (DE) was identified between morphs, throughout development. Additionally, Gene Ontology (GO) terms for DE genes were determined. Fewer genes were DE early in development compared to later in development, with more genes highly expressed in the gynoecium of the SS morph and the corolla and androecium of the LS morph. A reciprocal pattern was observed later in development, and many more genes were DE during this latter stage. During early development, DE genes appear to be involved in growth and floral development, and during later development, DE genes seem to affect physiological functions. Interestingly, many genes involved in response to stress were identified as DE between morphs.